New species of Anelosimus (Araneae: Theridiidae) from Africa and Southeast Asia, with notes on sociality and color polymorphism - Agnarsson, Ingi; Zhang, Jun-Xia (Zootaxa, 2006)
The cobweb spider genus Anelosimus contains species showing various levels of social behavior. American Anelosimus are well known and several species have been described from Europe, China, Japan, and Madagascar. However, to date, only two behaviorally unknown species have beendescribed from continental Africa, Southeast Asia, and Australasia combined. In this paper we describe seven new Anelosimus species, A. agnar n. sp. (Malaysia), A. biglebowski n. sp. (Tanzania), A. dude n. sp. (Tanzania), A. linda n. sp. (Malaysia), A. monskenyensis n. sp. (Kenya), A. nelsoni n. sp. (South Africa), and A. sulawesi n. sp. (Sulawesi) from Africa and Southeast Asia. We also redescribe A. kohi Yoshida, 1993 and provide evidence for subsocial behavior in that species. Anelosimus kohi shows a marked color polymorphism that is apparently habitat-related, both in populations in Malaysia and in Singapore. Several of the undescribed species were included in previous phylogenetic analyses, and the likely phylogenetic placement of each species is discussed. Based on new behavioral information we discuss the phylogenetic and geographical distribution of temporary and permanent sociality in Anelosimus.